1984
DOI: 10.1128/aem.47.4.724-730.1984
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of adherent epimural bacteria during succession in young lambs

Abstract: Successive changes in aerobic and anaerobic bacterial counts and changes in the generic composition of the epimural community in lambs from 1 to 10 weeks were determined. Bacterial culture counts revealed a predominantly anaerobic community, with the mean anaerobic count being 1.4 X 10(7) CFU/cm2 of tissue surface. The aerobic count was highest at 1 week of age and declined significantly thereafter to a mean of 1.8 X 10(4) CFU/cm2, thus representing only 0.13% of the mean anaerobic count after week 1. Of the 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…PCR-DGGE results are not indicative of population size, and quantitative biases associated with similar methods have been demonstrated [31]. However, these methods can be used to estimate species richness, or the number of species in a habitat [2,6,19,24,32]. Furthermore, results from culture-based and physiological studies are consistent with the hypothesis that a foal can possess a gastrointestinal microbial community in the climax state by 6 -12 weeks post parturition.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…PCR-DGGE results are not indicative of population size, and quantitative biases associated with similar methods have been demonstrated [31]. However, these methods can be used to estimate species richness, or the number of species in a habitat [2,6,19,24,32]. Furthermore, results from culture-based and physiological studies are consistent with the hypothesis that a foal can possess a gastrointestinal microbial community in the climax state by 6 -12 weeks post parturition.…”
Section: Discussionmentioning
confidence: 76%
“…[14][15][16][17][18][19][20]. By 6 weeks, calves have some of the same bacteria as adults, and by 9 -13 weeks, the bacteria isolated from calves were typical of those found in mature cattle [16,19]. Less is known about the colonization of equine gastrointestinal tract.…”
Section: Introductionmentioning
confidence: 99%
“…This community follows a characteristic succession, with significant changes occurring in the generic composition through the first 10 weeks of life. According to Mueller et al (1984b) , the epimural community does not appear to be markedly different taxonomically from the bacterial community of rumen contents, since most isolated strains could be placed into common rumen genera. However, recent studies conducted using molecular tools disagree with that statement.…”
Section: Factors That Influence the Microbiota Establishing In The Rumentioning
confidence: 99%
“…SBSEC members are estimated to contribute 10 6 to 10 7 cells per milliliter of rumen content (Hudson et al, 2000 ). Their prevalence in cattle is estimated between 20 and 90% with lowest prevalence at early ages (Jans et al, 2015 ) while in lambs an early live predominance of SBSEC is suggested (Mueller et al, 1984 ). Colonization and predominance is likely affected by feed composition as shown for reindeers where high SBSEC colonization correlates with higher quantities of starch-rich feed during the summer months (Orpin et al, 1985 ).…”
Section: Prevalence and Colonization Of Sbsec In Animals And Humansmentioning
confidence: 99%